Upaya Meningkatkan Kemampuan Mengenal Huruf Melalui Kartu Huruf Bergambar di TK Khadijah Al Kubro - Widya Nur Adha; Putri Asilestari; Citra Ayu (Jurnal Pendidikan Tuntas, 2024)
This research was motivated by the fact that children's letter recognition abilities at Khadijah Al-Kubro Kindergarten had not developed optimally. The problem in this research is "Can the use of picture letter card media improve the ability to recognize letters in the Khadijah Alkubro Bangkinang City Kindergarten?". The aim of the research is to determine the increase in the ability to recognize letters by using picture letter card media in the Khadijah Alkubro Bangkinang City Kindergarten. This research method is classroom action research (PTK) which was carried out in 2 cycles. This research was carried out from 29 August 2024 - 05 September 2024. The subjects in this research were children aged 5-6 years at Khadijah Al-Kubro Kindergarten, namely 15 children. Data collection in this research used observation and documentation sheets. The results of this research show that in cycle I there was an increase to 56% and in cycle II there was an increase to 87%. Thus, it can be concluded that the use of picture letter cards can improve the ability to recognize letters in children aged 5-6 years at Khadijah Al- Kubro Kindergarten.